The role of polyphenols and the cell wall in relation to the desiccation tolerance of the resurrection plant, Myrothamnus flabellifolia (Welw.) - Moore, John Paul (Department of Molecular and Cell Biology, 2014)
Includes bibliographical references (p. 160-191).